Implementation of group activity to solve academic Burnout elementary school students - Muhammad Nur Wangid; Isti Yuni Purwanti (Jurnal Prima Edukasia, 2020)
Academic burnout in elementary school students is very important to note because in this elementary school all academic experience will be formed. Failure to experience education in elementary schools properly will have a wide and disparate impact on the lives of students. This study aims to reduce the academic burnout experienced by elementary school students. For this reason, collaborative action research is conducted between teachers and researchers. Collaborative research, since planning, implementing, monitoring, and evaluating, as well as reflection is carried out jointly between teachers and researchers. The study subjects were five low-grade students who showed symptoms of experiencing academic burnout. Application of group activities as actions in the form of three games for students, namely picture puzzles, serialized stories, and throwing balls. Observation and interview as the main technique in collecting data. Qualitative analysis is used to analyze the process and results of actions. The results showed that the application of group activities was effective in reducing the academic burnout of five research subjects. All students showed positive changes in behavior, no longer showing symptoms of emotional fatigue, depersonalization, and feelings of inferiority or inadequacy. Research implications and recommendations are discussed.